Innovative microbial disease biocontrol strategies mediated by quorum quenching and their multifaceted applications: A review - Zhu, Xixian; Chen, Wen-Juan; Bhatt, Kalpana; Zhou, Zhe; Huang, Yaohua; Zhang, Lian-Hui; Chen, Shaohua; Wang, Junxia (Frontiers in Plant Science, 2023)
With the increasing resistance exhibited by undesirable bacteria to traditional antibiotics, the need to discover alternative (or, at least, supplementary) treatments to combat chemically resistant bacteria is becoming urgent. Quorum sensing (QS) refers to a novel bacterial communication system for monitoring cell density and regulation of a network of gene expression that is mediated by a group of signaling molecules called autoinducers (AIs). QS-regulated multicellular behaviors include biofilm formation, horizontal gene transfer, and antibiotic synthesis, which are demonstrating increasing pathogenicity to plants and aquacultural animals as well as contamination of wastewater treatment devices. To inhibit QS-regulated microbial behaviors, the strategy of quorum quenching (QQ) has been developed. Different quorum quenchers interfere with QS through different mechanisms, such as competitively inhibiting AI perception (e.g., by QS inhibitors) and AI degradation (e.g., by QQ enzymes). In this review, we first introduce different signaling molecules, including diffusible signal factor (DSF) and acyl homoserine lactones (AHLs) for Gram-negative bacteria, AIPs for Gram-positive bacteria, and AI-2 for interspecies communication, thus demonstrating the mode of action of the QS system. We next exemplify the QQ mechanisms of various quorum quenchers, such as chemical QS inhibitors, and the physical/enzymatic degradation of QS signals. We devote special attention to AHL-degrading enzymes, which are categorized in detail according to their diverse catalytic mechanisms and enzymatic properties. In the final part, the applications and advantages of quorum quenchers (especially QQ enzymes and bacteria) are summarized in the context of agricultural/aquacultural pathogen biocontrol, membrane bioreactors for wastewater treatment, and the attenuation of human pathogenic bacteria. Taken together, we present the state-of-the-art in research considering QS and QQ, providing theoretical evidence and support for wider application of this promising environmentally friendly biocontrol strategy.